Relationship between Music Education and Academic Performance in Elementary Schools in Jamaica - Rodney, David (American Journal of Arts, Social and Humanity Studies, 2024)
Purpose: The aim of the study was to assess the relationship between music education and academic performance in elementary schools in Jamaica. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that students who participate in music education tend to have higher academic achievement across various subjects, particularly in mathematics and language arts. Music education enhances cognitive abilities such as memory, attention, and spatial-temporal skills, which contribute to better problem-solving and reasoning capabilities. Additionally, engaging in music activities fosters discipline, improves social skills, and enhances self-esteem, all of which are conducive to a more effective learning environment. These benefits collectively support the notion that music education can play a crucial role in the holistic development of young students, leading to improved academic outcomes. Implications to Theory, Practice and Policy: Multiple intelligences theory, socio-cultural theory and flow theory may be used to anchor future studies on assessing the relationship between music education and academic performance in elementary schools in Jamaica. Design music education curricula with comprehensive depth and diverse learning experiences to enhance critical thinking, creativity, and academic engagement among elementary school students. Advocate for the integration of music education into the core curriculum of elementary schools, recognizing its significant contributions to cognitive development, academic achievement, and overall student well-being.